Effect of silica fume on the properties of sustainable cement concrete - Hamada H.M.; Abed F.; Binti Katman H.Y.; Humada A.M.; Al Jawahery M.S.; Majdi A.; Yousif S.T.; Thomas B.S. (Elsevier Editora Ltda, 2024)
The disposal of hazardous waste materials in landfills and open areas creates a severe impact on the environment. Silica Fume (SF), a by-product from the ferrosilicon and silicon industry, is generated in high quantities. Recent studies have highlighted the advantages of reusing SF to produce high-strength concrete (HSC) and ultra-high-performance concrete (UHPC) instead of discarding it. This paper herein reviews the current research on SF in concrete and discusses the physical and chemical properties, mechanical properties, durability, and microstructure. Depending on the concentration of the SF, flexural, tensile, and compressive strength was positively influenced. Also, SF improved the pore size to increase drying shrinkage through the pozzolanic reaction. A few studies showed the disadvantages of SF exhibiting the negative impact on workability and shrinkage of concrete. The influence of SF on cement hydration products should be analyzed from the microstructure perspective. 2023 The Author(s)